Keadaan Insolvensi Dalam Permohonan Pailit Perusahaan Sebagai Upaya Menjaga Kepentingan Kreditor dan Debitor Menurut UU No. 37 Tahun 2004 Tentang Kepailitan dan PKPU - Annisa Egis Agnesia; Christine S.T Kansil (Syntax Corporation, 2022)
The Indonesian Bankruptcy Law (The Law Number 37 of 2004 concerning Banckrupcty and Postponement of Debt Payment Obligations (PKPU)) needs to be amended several times following the increasingly global demands of business and investment changes. The application of the principle of insolvency in a company's bankruptcy application can be one of the steps to improve the bankruptcy climate in Indonesia so as to attract investors to invest their capital.